Corporate mergers and accounting performance during a period of economic crisis: evidence from Greece - Pazarskis, Michail; Vogiatzoglou, Manthos; Koutoupis, Andreas; Drogalas, George (Journal of Business Economics and Management, 2021)
Merger deals are one of the most important business strategies which can change the company value dramatically. Mergers have been constantly a subject of debate and analysis over the past decades. Thus, it is a matter of great interest to analyze merger activities during economic crisis periods, as it was in Greece recently. This paper explores the accounting performance of Greek listed companies after mergers in 2009–2015, the economic crisis period in Greece. Thus, all mergers of listed companies during the above period are initially examined through several financial ratios from financial statements for one year before and after the merger. The analysis of Greek listed companies that comprise the final sample is performed with several regression models. The study provides positive and statistically significant results for mergers, in the sense that the period of crisis that the merger took place is positively correlated with several performance measures. Regarding the industry relatedness, the study provides evidence that conglomerate mergers have more positive impact to the improvement of the companies’ profitability than non-conglomerate mergers. Last, for the merger events that take place far from the climax of the economic crisis, the profitability of merged companies is increased.